Feeding Mara: An Examination of Redemption in the Book of Ruth - Valentine, Chesirae (Lumen et Vita, 2018)
Traditionally understood as an exercise in feminist theology or political storytelling, the Book of Ruth’s ministerial potential remains untapped. Ruth acts as more than a feminist icon or political example when she redeems Mara — she acts as the hands of God. Though often read through a historical or feminist lens, I propose that the Book of Ruth is primarily a liberation text, answering Ignacio Ellacuría’s question: “What must I do to uncrucify [the suffering]?” When Naomi becomes Mara, she becomes representative of every person who has suffered under systemic oppression. Ruth, by meeting Naomi in her pain and answering it, becomes representative of God. The path to Naomi’s redemption then becomes the path the Church might tread to serve, liberate, and comfort those who are systematically oppressed. Ruth ultimately redeems Naomi through three actions. First, by pledging solidarity of experience with Naomi, Ruth promises to trust Naomi/Mara’s experiences as valid and worthy, and does not presume to narrate Mara’s suffering. Second, by listening to and providing for Mara’s needs, Ruth does not presume to pity, but rather to understand and liberate Mara’ s immediate suffering. Third, by trusting Mara’ s needs and experiences, Ruth can comfort Naomi through creating a new system: a new family through Obed. By creating a new space where Mara is freed from her bitterness, Naomi can exist once again. The Book of Ruth becomes a parable that explores the way God’s compassion may work in and through human systems to redeem the oppressed. This article explores that parable, and begins to answer how the Church — as God’s earthly hands — might begin to do this work for systematically oppressed people.